Russia's theatrical past court entertainment in the seventeenth century - Jensen, Claudia Rae (Russian music studies, 2021)
Russia's Theatrical Past, made possible by an international research collaborative, offers fresh insight into how and why Russians went to such great efforts to rapidly develop court theater in the 17th century.